THE CORRELATION BETWEEN PREGNANT WOMEN BEHAVIOR WITH COVID-19 IN PREGNANT WOMEN IN TAMBAKBOYO PUBLIC HEALTH CENTER AREA - Munir, Miftahul; Qonitun, Umu; Nikmah, Siti Ima'tul (Department of Midwifery, Faculty of Nursing and Midwifery, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2021)
The COVID-19 pandemic has caused disruptions to health, economy, politics, and social order worldwide. Pregnant women experience physiological and immunological changes and are one of the vulnerable groups with high comorbidity rates. This study was conducted to determine the relationship between the behavior of pregnant women and the incidence of COVID-19 in the Tambakboyo Health Center area. This was an analytic observational with a quantitative approach research. With data taken through questionnaires and the results of RT-PCR and antigen swab analysis used a cross-sectional time approach with the population being pregnant women who were screened in the Tambakboyo Health Center area in June 2020 - May 2021 with a sample of 160 respondents determined by the Probability Sampling technique. sample used simple random sampling. The independent variable in this study was the behavior of pregnant women, while the dependent variable was the incidence of COVID-19 in pregnant women in the Tambakboyo Health Center area. The analysis carried out using the Chi-square test with the significance level of the test results obtained a significance value of p = 0.000 which means that it showed that there was a correlation between the behavior of pregnant women and the incidence of COVID-19.